PENINGKATAN KEMAMPUAN WUDHU DAN SHALAT FARDHU MELALUI METODE MODELLING THE WAY - Bilkis Islami, Tasy; Lubis, Rabiyannur; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
This community service activity aims to provide teaching and guidance in carrying out ablutions and fard prayers by practicing them directly through the modelling the way method. The problem that often occurs is that there are still many children who perform ablutions and prayers in a joking and disorderly manner. So that prayer training is important from an early age through Islamic religious education. However, teachers often deliver learning in a monotonous way so that children easily feel bored and bored. The methods used in this activity include socialisation, training and mentoring. This activity was carried out at MI Al-Islamiyah 02 Nagabuat Village with the target of 40 6th grade students. The result of this activity is an increase in students' skills and abilities in performing ablutions and fard prayers. So it can be concluded that this programme can have a significant positive impact on students. Thus, the author suggests that educators can pay attention to the methods and media that will be used in delivering material in the classroom in order to achieve learning objectives and effectiveness.